The Comparative Study: Protecting Children’s Rights Through Law Reform of Restorative Justice in Juvenile Cases - Ismail, Dian Ekawaty; Ahmad, Nadzriah; Mantali, Avelia Rahmah Y.; Moha, Mohamad Rivaldi; Machmud, Andika Wardhana (Journal of Law and Legal Reform, 2025)
The high influence of the internet plays a role in the increase in criminal acts that use children as the main perpetrators. In legal involvement on the part of the child as a suspect, the law must consider the mental aspects of the child. Children who come into contact with the law are often confronted with the Juvenile Justice System (JJS). The judge’s decision following the trial can have negative effects on the child. Restorative Justice through the implementation of Diversion is a step that law enforcement officials can take to prevent children from facing trial situations. This study aims to examine the implementation of Restorative Justice in juvenile cases and analyze its role in shaping character and safeguarding children’s rights amid the challenges of the digital era. This research used normative legal research by examining literature studies from primary and secondary legal materials. The results of this research indicate that the implementation of Restorative Justice in juvenile cases can be carried out in the Pre-Adjudication stage (investigation and inquiry), Adjudication stage (prosecution and trial), and Post-Adjudication stage (execution of sentences). Meanwhile, the implementation of Restorative Justice in building character and protecting children’s rights can be achieved through the integration of restorative justice principles, including education and awareness, rehabilitation approach, active participation of children, involvement of victims, use of alternative sanctions, collaboration with experts, respecting children, and developing social and emotional skills.